Atratividade cultural e potencialidade turística: análise do evento Auto de Natal (Natal RN) - Cunha, Shirley de Lima (2013)
Inserted in the schedule for Christmas celebration in the city of Natal, capital of the state of Rio Grande do Norte, Brazil, the spectacle so called Auto de Natal mixes the Christmas story of Jesus birth with cultural and natural heritage of the state, making possible the integration of professionals from various fields, such as: literature, theater, dance and music. Important for local identity, Auto de Natal integrates elements of intangible heritage in the state. In this context, the research analyzed the perceptions of those who were involved in the production, presentation and organization of the event, planned to be culturally attractive to tourism. For this, it was used the descriptive and exploratory method, making use of documental, bibliographic and field researches. It was applied qualitative techniques to the interpretation of the interviews, while it was applied quantitative techniques to analyze the questionnaires. The research has discovered that Auto de Natal has the potential to add value to Cultural Tourism, diversifying the tourism product. The research has also observed that most of the respondents recognized Auto de Natal as intangible heritage, and concluded that the Christmas theme, which is alluding to the nomenclature of destiny, needs to be well-done to attract more tourists to experience the Natal in Natal